Epigenetic influences in the developmental origins of osteoporosis. - Holroyd, C; Harvey, N; Dennison, E; Cooper, C (2012)
Osteoporosis is a major public health problem due to consequent fragility fractures; data from the UK suggest that up to 50% of women and 20% men aged 50 years will have an osteoporosis-related fracture in their remaining lifetime. Skeletal size and density increase from early embryogenesis through intrauterine, infant, childhood and adult life to reach a peak in the third to fourth decade. The peak bone mass achieved is a strong predictor of later osteoporosis risk. Epidemiological studies have demonstrated a positive relationship between early growth and later bone mass, both at peak and in later life, and also with reduced risk of hip fracture. Mother-offspring cohorts have allowed the elucidation of some of the specific factors in early life, such as maternal body build, lifestyle and 25(OH)-vitamin D status, which might be important. Most recently, the phenomenon of developmental plasticity, whereby a single genotype may give rise to different phenotypes depending on the prevailing environment, and the science of epigenetics have presented novel molecular mechanisms which may underlie previous observations. This review will give an overview of these latter developments in the context of the burden of osteoporosis and the wider data supporting the link between the early environment and bone health in later life.